Preparation of Zinc Oxide Nanoparticles and its Characterization Using Scanning Electron Microscopy (SEM) and X-Ray Diffraction(XRD). (2016) - Mohan, Ananthu C.; Renjanadevi, B.
Abstract: Zinc oxide can be called a multifunctional material thanks to its unique physical and chemical properties. The main objective of this paper is the preparation of zinc oxide nanoparticles using conventional methods and the preparation using surfactant. The first part of this paper presents the different methods of preparation of Zinc oxide nanoparticles using different precursors and its surface modification using Poly Vinyl Alcohol (PVA). The next part of this paper deals with characterization of the prepared zinc oxide using Scanning Electron Microscopy (SEM) and X-Ray Diffraction in order to determine which method is more feasible in terms of particle agglomeration, particle size, particle separation.